2016
DOI: 10.1371/journal.pone.0148542
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Prevent Renal Fibrosis in a Rat Model of Unilateral Ureteral Obstruction by Suppressing the Renin-Angiotensin System via HuR

Abstract: We studied Mesenchymal Stromal Cells (MSC) effects in experimental Unilateral Ureteral Obstruction (UUO), a fibrogenic renal disease. Rats were divided in 5 groups: sham, UUO, MSC treated-UUO, ACEi treated-UUO, MSC+ACEi treated- UUO. Data were collected at 1, 7, 21 days. UUO induced monocyte renal infiltration, tubular cell apoptosis, tubular atrophy, interstitial fibrosis and overexpression of TGFβ, Renin mRNA (RENmRNA), increase of Renin, Angiotensin II (AII) and aldosterone serum levels. Both lisinopril (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 64 publications
1
27
0
1
Order By: Relevance
“…Several studies have demonstrated that MSCs can protect against acute and chronic renal injury (1,8,28), and, while the mechanism of MSC-induced renal protection remains unknown, recent studies suggest that a significant component of MSC's protective and reparative function resides in their paracrine activity. MSCs can secrete a number of growth factors and cytokines that are important for angiogenesis and cytoprotection and have been demonstrated to prevent tubulointerstitial fibrosis during chronic unilateral ureteral obstruction (UUO) (2,5,9).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that MSCs can protect against acute and chronic renal injury (1,8,28), and, while the mechanism of MSC-induced renal protection remains unknown, recent studies suggest that a significant component of MSC's protective and reparative function resides in their paracrine activity. MSCs can secrete a number of growth factors and cytokines that are important for angiogenesis and cytoprotection and have been demonstrated to prevent tubulointerstitial fibrosis during chronic unilateral ureteral obstruction (UUO) (2,5,9).…”
mentioning
confidence: 99%
“…MSC were isolated from bone marrow of EGFP transgenic SD rats, expanded in vitro and used at P2/P3 as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…EGFP‐rat MSC, hereafter referred to as MSC, were characterized for plastic adhesion, morphology, antigen surface expression of CD49e, CD90 and CD29 and the absence of CD45 and CD11b (all antibodies were purchased from BioLegend, San Diego, CA, USA) performed with a Navios flow cytometer (Beckman Coulter, Milan, Italy) and differentiation capacity .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, IL-10 also appears to have an effect on profibrotic signaling pathways that are unique to the kidney, specifically that mesenchymal stromal cell-released IL-10 inhibited RAAS signaling and thereby reduced tubular scarring after unilateral ureteral obstruction (UUO). 93 As in the heart, the molecular mechanism behind this effect appeared to be a decrease in inflammatory cytokine mRNA due to HuR transcription inhibition. Similarly, our laboratory has shown that exogenous IL-10 administration post-UUO attenuates tubulointerstitial fibrosis and is additionally associated with upregulated HMW-HA, similar to the effects seen with IL-10 in the skin.…”
Section: Renal Fibrosismentioning
confidence: 99%